A quarter century of biomonitoring atmospheric pollution in the Czech Republic - Suchara, Ivan; Sucharová, Julie; Holá, Marie (Environmental science and pollution research international, 2017)
The Czech Republic (CZ) had extremely high emissions and atmospheric deposition of pollutants in the second half of the 1980s. Since the beginning of the 1990s, moss, spruce bark and forest floor humus have been used as bioindicators of air quality. In the first half of the 1990s, seven larger areas were found to be affected by high atmospheric deposition loads. Six of these "hot spots" were caused by industrial pollution sources, mainly situated in coal basins in the NW and NE part of the country, and one large area in the SE was affected by increased deposition loads of eroded soil particles. After restructuring of industry in CZ, these hot spots were substantially reduced or even disappeared between 1995 and 2000. Since 2000, only two larger areas with slightly increased levels of industrial pollutant deposition and a larger area affected by soil dust have repeatedly been identified by biomonitoring. The distribution of lead isotope ratios in moss showed the main deposition zones around important emission sources. Very high SO2 emissions led to extreme acidity of spruce bark extracts (pH of about 2.3) at the end of the 1980s. The rate of increasing bark pH was strikingly similar to the rate of recovery of acid wet deposition measured at forest stations in CZ. By about 2005, when the median pH value in bark increased to about 3.2, the re-colonisation of trees by several epiphyte lichen species was observed throughout CZ. An increase in the accumulation of Chernobyl-derived 137Cs in bark was detected at about ten sites affected by precipitation during the time when radioactive plumes crossed CZ (1986). Accumulated deposition loads in forest floor humus corresponded to the position of the moss and bark hot spots.
Keywords: Moss; Czech Republic; Picea; látky znečišťující vzduch; Forest humus; Česká republika; smrk; půda; Environmental Monitoring; Plant Bark; Air pollution; Bioindicators; monitorování životního prostředí; Air Pollutants; Soil; kůra rostlin; Spruce bark; Bryophyta